Correlation Between Chronic Pain Acceptance and Clinical Variables in Ankylosing Spondylitis and Its Prediction Role for Biologics Treatment - Li, Ting; Liu, Yaqun; Sheng, Rong; Yin, Jian; Wu, Xin; Xu, Huji (Frontiers in Medicine, 2020)
Objectives: Studies have proven that improving patients' acceptance of chronic pain could be an effective therapy for alleviating pain and other symptoms. Our objectives were to investigate the correlation between chronic pain acceptance and clinical variables in ankylosing spondylitis (AS), and the prediction role of chronic pain acceptance for biologics treatment. Methods: First, 167 AS patients were recruited to complete a series of questionnaires, including the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index (BASFI), Chronic Pain Acceptance Questionnaire (CPAQ), Hospital Anxiety and Depression Scale (HADS), and Tampa Scale for Kinesiophobia (TSK). Bivariate correlation analysis was utilized to investigate the correlation between pain acceptance and clinical variables. Based on the level of chronic pain acceptance and serum C-reactive protein (CRP), patients were separated into four subgroups. Then, another 68 patients initiating anti-tumor necrosis factor (TNF) treatment were recruited to complete the questionnaires at baseline (T0) and 3 months after treatment (T3). The changes in clinical variables and treatment response were compared between multiple subgroups. Results: Chronic pain acceptance had strong correlations with anxiety, depression and fear of movement, and moderate correlations with BASFI and pain intensity. Both activity engagement (AE) and pain willingness (PW) had significant correlations with pain intensity, BASFI and psychological status. In addition, AE had a significant correlation with disease duration, while PW had a significant correlation with ASDAS-CRP. Subgroup analysis showed that patients with low chronic pain acceptance and high levels of serum CRP had the highest BASDAI. Among patients initiating anti-TNF treatment, those with high pain acceptance and high levels of serum CRP achieved the most obvious reduction in BASDAI after 3 months treatment. Conclusion: Pain acceptance is a new tool to assess pain in AS which may also reflect physical and psychological status. Clinicians should identify high-risk patients with low chronic pain acceptance and high levels of serum CRP, and give psychological and pharmacological intervention promptly. Moreover, the combination of baseline chronic pain acceptance and serum CRP level could be used to predict the treatment response in AS patients initiating biologics treatment.